EFFECT OF EXOGENOUSE LOCAL LIGNINOLYTIC CRUDE ENZYMES ON IN VITRO DIGESTABILITY AND LIGNIN CONTENT OF ROUGHAGES - & Al-Khateeb, Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In current study use local ligninolytic crude extract enzyme (HAMU 8%) to improve IVDMD and reducing lignin content. The result suggest that treated wheat straw (WS), Corncobs (Cc), alfalfa hay (AH), by HAMU increased significantly (p